Advances in Stigmasterol on its anti-tumor effect and mechanism of action - Zhang, Xiaoyu; Wang, Jiayun; Zhu, Lin; Wang, Xuezhen; Meng, Feifei; Xia, Lei; Zhang, Hairong (Frontiers in Oncology, 2022)
Stigmasterol is a phytosterol derived from multiple herbaceous plants such as herbs, soybean and tobacco, and it has received much attention for its various pharmacological effects including anti-inflammation, anti-diabetes, anti-oxidization, and lowering blood cholesterol. Multiple studies have revealed that stigmasterol holds promise as a potentially beneficial therapeutic agent for malignant tumors because of its significant anti-tumor bioactivity. It is reported that stigmasterol has anti-tumor effect in a variety of malignancies (e.g., breast, lung, liver and ovarian cancers) by promoting apoptosis, inhibiting proliferation, metastasis and invasion, and inducing autophagy in tumor cells. Mechanistic study shows that stigmasterol triggers apoptosis in tumor cells by regulating the PI3K/Akt signaling pathway and the generation of mitochondrial reactive oxygen species, while its anti-proliferative activity is mainly dependent on its modulatory effect on cyclin proteins and cyclin-dependent kinase (CDK). There have been multiple mechanisms underlying the anti-tumor effect of stigmasterol, which make stigmasterol promising as a new anti-tumor agent and provide insights into research on its anti-tumor role. Presently, stigmasterol has been poorly understood, and there is a paucity of systemic review on the mechanism underlying its anti-tumor effect. The current study attempts to conduct a literature review on stigmasterol for its antitumor effect to provide reference for researchers and clinical workers.